A novel germline variant in the DOT1L gene co-segregating in a Dutch family with a history of melanoma. Issue 6 (December 2019) - Salgado, Catarina; Kwesi-Maliepaard, Eliza Mari; Jochemsen, Aart G.; Visser, Mijke; Harland, Mark; van Leeuwen, Fred; van Doorn, Remco; Gruis, Nelleke
Abstract : A proportion of patients diagnosed with melanoma has a positive family history. Despite increasing knowledge on the genes responsible for familial clustering, the genetic basis in the majority of the families with an inherited predisposition to melanoma remains to be clarified. To identify novel melanoma-susceptibility genes, we applied whole-exome sequencing on DNA from two members of a family with four melanoma cases, not explained by established high penetrance melanoma-susceptibility genes. Whole-exome sequencing identified 10 rare, co-segregating, predicted deleterious missense gene variants. Subsequent co-segregation analysis revealed that only variants in the DOT1L (R409H) and the SLCO4C1 (P597A) genes were present in the other two affected members of this family. DOT1L is a methyltransferase that methylates histone H3 lysine 79 (H3K79). It is involved in maintenance of genomic stability, since mutations in the DOT1L gene have been previously reported to compromise the removal of ultraviolet photoproducts in ultraviolet-irradiated melanocytes, thereby enhancing malignant transformation. We hypothesized that the presence of DOT1L R409H variant might be associated with an increased risk of melanoma, since we found co-segregation of the DOT1L mutation in all four melanoma-affected family members. However, this missense variant did neither lead to detectable loss-of-heterozygosity nor reduction of histone methyltransferase activity in melanoma samples from mutation carriers nor altered ultraviolet-survival of mouse embryonic stem cells containing an engineered homozygous DOT1L R409H mutation. Although functional analysis of this rare co-segregating variant did not reveal compromised histone methyltransferase activity and ultraviolet exposure sensitivity, the role of DOT1L as melanoma susceptibility gene deserves further study. Abstract : Supplemental Digital Content is available in the text.